Linseed: An oilseed crop with multiple uses - Singh, Ranbir; Singh, T P; Dutta, M (Indian Farming, 2015)
Linseed is an oilseed crop of significant economic importance. Ithas various uses for the industrial, medicinal, nutritional and ornamental purposes. Being a multipurpose crop, there is an urgent need to increase the area under its cultivation for increasing the productivity of this crop.